0827 The Association Among Diagnosed and Suspected Sleep Disorders and Pain. (27th May 2020) - Ravyts, S; Dzierzewski, J
Abstract: Introduction: Poor sleep has increasingly been linked to adverse pain outcomes. Yet, the complex interplay between sleep apnea, insomnia, or comorbid sleep apnea and insomnia (COMISA), and pain are less well understood. The purpose of the present study was twofold: 1) assess pain intensity in individuals with diagnoses of insomnia, sleep apnea, and COMISA, and 2) examine pain intensity in individuals who are at a high risk for having either sleep apnea, insomnia, or both sleep disorders. Methods: Participants included 3401 adults (mean age= 42.77, male= 45.6%) who participated in an online study investigating sleep across the lifespan. Sleep apnea and insomnia diagnoses were self-reported while participant risk profiles for these disorders were assessed via the Insomnia Severity Index and the STOP-BANG questionnaire respectively. Average pain intensity over the last two weeks was rated from 0 ( no pain ) to 100 ( very severe ). Results: Participants with self-reported comorbid sleep disorders reported higher pain scores than individuals with one or no sleep disorder ( F (2, 3398) = 71.61, p < .001). Among individuals with no previously diagnosed sleep disorder, participants with more insomnia symptoms reported greater pain intensity ( F (3, 3100) = 201.64, p < .001), as did those with higher scores on the STOP-BANG ( F (2, 3125) = 46.79, p < .001). Participants with suspected comorbid sleep disorders reported higher pain scores than individuals with either sleep apnea or no sleep disorder, but not insomnia ( F (3, 2887) = 110.15, p < .001). Conclusion: Results suggest that individuals with known sleep disorders report high levels of pain particularly in the context of comorbid sleep apnea and insomnia. Additionally, individuals with suspected, but untreated, sleep disorders also report increased pain. Future research should examine whether treating one of more sleep disorders can improve pain outcomes. Support: This work was supported by the National Institute on Aging (K23AG049955, PI: Dzierzewski).